Future Control Room Improvements : Government update on fire and rescue authority schemes. Ex-Fire Regional Control Centres - marketing and disposal. March 2015 update.: Government update on fire and rescue authority schemes. Ex-Fire Regional Control Centres - marketing and disposal. March 2015 update. (March 2015) - Great Britain., Department for Communities and Local Government,
No abstract available